VR-assisted aggression treatment in forensic psychiatry: a qualitative study in patients with severe mental disorders - González Moraga, Fernando Renee; Enebrink, Pia; Perrin, Sean; Sygel, Kristina; Veling, Wim; Wallinius, Märta (Frontiers in Psychiatry, 2024)
Improvements in vVirtual rReality (VR) have made it possible to create realistic, virtual settings for behavioral assessment and skills training that cannot otherwise be accessed in a safe way in forensic psychiatric settings. VR interventions are under development but little is known how forensic psychiatric patients with severe mental disorders experience VR-assisted assessments or treatments.The present study aimed to help fill this knowledge gap via qualitative interviews with seven patients with severe mental disorders at a high-security forensic psychiatric clinic who had completed the newly revised Virtual Reality Aggression Prevention Training (VRAPT). All participants were interviewed 12 weeks after the VRAPT intervention, and interview data analysed with manifest inductive content analysis. Six manifest content categories were identified: 1. Therapeutic process, 2. VRAPT method, 3. VR technology, 4. Previous treatment experiences, 5. Challenges to treatment of aggression, and 6. Unexpected experiences. The participants had diverse experiences related to both the VRAPT intervention and forensic psychiatric care. Participants described a mixture of positive experiences in relation to VR-assisted role-plays, and less positive in relation to motivation for aggression-focused treatment and technological limitations. The present findings suggest further studies are needed on how to best implement VR-assisted treatments for aggression in forensic settings, and potentially further modification of treatment content in interventions like VRAPT.